2013
DOI: 10.1186/1471-2458-13-1082
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Use of H1N1 and seasonal influenza vaccinations between veterans and non-veterans in the United States, 2010

Abstract: BackgroundVeterans of the U.S. armed forces tend to be older and have more chronic health problems than the general adult population, which may place them at greater risk of complications from influenza. Despite Centers for Disease Control and Prevention (CDC) recommendations, seasonal influenza vaccination rates for the general adult population remain well below the national goal of 80%. Achieving this goal would be facilitated by a clearer understanding of which factors influence vaccination.MethodsUsing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…All of the studies in this category used more than one measure to capture SES and reported inconsistent results on the association between influenza and SES. Seven studies used two measures [27, 31, 32, 34, 35, 38, 42] and five studies used three measures or a composite measure combining three or more measures of SES [4347].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All of the studies in this category used more than one measure to capture SES and reported inconsistent results on the association between influenza and SES. Seven studies used two measures [27, 31, 32, 34, 35, 38, 42] and five studies used three measures or a composite measure combining three or more measures of SES [4347].…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies that employed three measures of SES to separately capture the effects of education, income, and employment or class, four reported mixed positive and negative associations and two reported consistent associations. Among US adults, Der-Martirosian et al (2013) found that education level was positively associated with H1N1 and seasonal influenza vaccination, while income was only associated with seasonal influenza vaccination, and employment status was associated with neither [43]. In Leuven, Belgium, a survey of pregnant women in their third trimester found that only education was positively and significantly associated with vaccination [44].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These seemingly controversial findings, together with misleading information on social media, may confuse the public, particularly smokers, thus may influence their acceptance of a COVID-19 vaccine. Nonetheless, evidence for other vaccines such as influenza suggests that smokers may be less likely than others to be vaccinated [17,18]. Accordingly, understanding which subgroups of smokers might be more or less likely to be vaccinated for COVID-19 would permit the development of more targeted interventions aimed at boosting vaccine uptake among users of tobacco and perhaps marijuana.…”
Section: Introductionmentioning
confidence: 99%